Gallipoli - Moorehead, Alan, 1910-1983 (London Hamish Hamilton, 1967)
Two friends are involved with the battle between Australia and the German-occupied Turks in this commentary on the wastes of war.
Include Pictures and Index
Keywords: Military Campaigns -- Battlefields -- Turkey--Gallipoli